The visual rhetoric in comics for reader interpretation and engagement to meaning-making in the medium - Muliyati Mat Alim,; Ida Puteri Mahsan,; Mohd Fauzi Harun,; Mohd Yusof Zulkefli, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Comics are a unique form of sequential art that combines text and visual graphics to tell a story. In academic circles, the purposeful use of visual elements to convey meaning or visual rhetoric has been gaining increasing attention. This research explores how comics' use of visual rhetoric affects readers' interpretations of and interactions with the medium. Additionally, the study seeks to explore how the discussion about models and concepts used affects readers' interactions with the medium and their meaning-making processes. To achieve this, the research employed qualitative methods, using descriptive and semi-systematic approaches to gather information on visual rhetoric related to three predetermined objectives. The study's results advance the field of comics studies by offering new insights into the potential of visual rhetoric to convey complex ideas and abstract concepts. It also contributes to the academic study of comics by providing fresh perspectives on using visual rhetoric to convey complex ideas. Overall, this research offers a better understanding of the interplay between visual elements and textual components in comics, helping readers better appreciate the medium's storytelling capabilities. Through a detailed analysis of comics and their visual rhetoric, this study sheds light on the nuanced ways in which visual elements contribute to meaning-making in the medium. The findings of this research have implications for educators, artists, and scholars interested in understanding the role of visual rhetoric in communication and storytelling.